X‐ray bi‐prism interferometry—A design study of proposed novel hardware. Issue 10 (11th October 2021) - Gullberg, Grant T.; Shrestha, Uttam; Kim, Sally Ji Who; Seo, Youngho; Fuller, Michael
Abstract: Purpose: Advances in X‐ray phase‐contrast imaging can obtain excellent soft‐tissue contrast of phase‐shift, attenuation, and small‐angle scatter. Here, we present fringe patterns for different design parameters of X‐ray bi‐prism interferometry imaging systems. Our aim is to develop bi‐prism interferometry imaging systems with excellent polychromatic performance that produce high‐contrast fringes with spatially incoherent X‐ray illumination. We also introduce a novel X‐ray tube design that uses temporal multiplexing to provide simultaneous virtual "electronic phase stepping" that replace "mechanical phase stepping" popular with grating‐based interferometry setups. Methods: In our investigation, we develop expressions for the irradiance distribution pattern of a bi‐prism interferometer composed of multiple point sources and multiple bi‐prisms. These expressions are used to plot fringe patterns for X‐ray design parameters, including size of point source, number of point sources, and point source separation, and bi‐prism design parameters including material, angle, number of bi‐prisms, period, and bi‐prism array to X‐ray source and detector distances. Results: Results show that the fringe patterns for a bi‐prism interferometry system are not longitudinally periodic as with grating interferometers that produce a Talbot–Lau carpet. It is also shown that at 59 keV X‐rays the bi‐prism material should be something comparable to nickel to obtain reasonable fringe visibility. Conclusion: The irradiance distribution pattern demonstrates that bi‐prism interferometry may provide comparable or improved fringe visibility to that of gratings. Special care is given to present our findings within the context of previous advancements. A single‐shot image acquisition approach using a temporal multiplexed, high‐power X‐ray source provides virtual electronic phase stepping without focal spot sweeping. This provides multiple images, each at the same exposure and the same projection view, from different fringe locations that allow one to derive the attenuation, phase, and dark‐field images of the sample without mechanical phase stepping of a grating.